Penerapan Pembelajaran Matematika Materi Geometri di SDN 34/I Muara Bulian - Yesi Desria; Ilhan Manzis; Devi Aulia Ulva; Syahrial Syahrial; Silvina Noviyanti (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
The problem of this research is how the process of learning mathematics on geometry material is easy to understand, enjoy, and does not make students feel bored with the material so that it can lead students to academic achievement at national and international levels. The purpose of this study is to describe the planning, implementation, evaluation, and obstacles in learning mathematics with geometry material. The research method uses descriptive qualitative. Data collection techniques are semi-structured interviews, non-participating observations, and documentation studies. The subjects of the study were lecturers of geometry experts, school principals, fifth grade mathematics teachers, and fifth grade students. The results showed that the planning, implementation, and evaluation of mathematics learning for class V gemoteri materials went well, coherently, pleasantly and without obstacles. meaning for both teachers and students.